2011
DOI: 10.1007/978-1-4020-9212-1_162
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost Microbiology

Abstract: Numerous and various ecological and morphological groups of viable micro-organisms survive under permafrost conditions. They are the only known living organisms preserved over a geologically significant time. Their preservation within permafrost is of interest from both biological and geocryological points of view and forms the basis for a number of investigations in different scientific fields. The latter are performed not only upon morphological but also upon functional characteristics of viable cells. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 75 publications
2
27
0
Order By: Relevance
“…Recently, metagenomic efforts have shed light on the permafrost microbiome in some parts of Arctic such as Alaska [25], Svalbard [26], Canadian Arctic [27,28], and Greenland [29]. A wide diversity of culturable bacteria representing over 30 genera including Acinetobacter, Aeromonas, Alcaligenes, Arthrobacter, Bacillus, Brevibacterium, Cytophaga, Clostridium, Cellulomonas, Deinococcus, Exiguobacterium, Flavobacterium, Glaciimonas, Kocuria, Micrococcus, Mycobacteria, Myxococcus, Nitrobacter, Nitrosomonas, Nitrosospira, Paenibacillus, Promicromonospora, Pseudomonas, Psychrobacter, Rhodococcus, Serratia, Sporosarcina, Subtercola, and Streptomyces have been isolated from Arctic permafrost [10,17,19,22,23,30]. Furthermore, Hansen et al [31] and Variovorax) employing culture-dependent and culture independent methods from the permafrost soil of Spitsbergen (78°12′N, 15°50′E).…”
mentioning
confidence: 99%
“…Recently, metagenomic efforts have shed light on the permafrost microbiome in some parts of Arctic such as Alaska [25], Svalbard [26], Canadian Arctic [27,28], and Greenland [29]. A wide diversity of culturable bacteria representing over 30 genera including Acinetobacter, Aeromonas, Alcaligenes, Arthrobacter, Bacillus, Brevibacterium, Cytophaga, Clostridium, Cellulomonas, Deinococcus, Exiguobacterium, Flavobacterium, Glaciimonas, Kocuria, Micrococcus, Mycobacteria, Myxococcus, Nitrobacter, Nitrosomonas, Nitrosospira, Paenibacillus, Promicromonospora, Pseudomonas, Psychrobacter, Rhodococcus, Serratia, Sporosarcina, Subtercola, and Streptomyces have been isolated from Arctic permafrost [10,17,19,22,23,30]. Furthermore, Hansen et al [31] and Variovorax) employing culture-dependent and culture independent methods from the permafrost soil of Spitsbergen (78°12′N, 15°50′E).…”
mentioning
confidence: 99%
“…In addition to the soil physical characteristics discussed above, pore water geochemical analysis provides valuable information for understanding its potential impacts on soil biogeochemical processes during permafrost thaw. Previous studies on saline permafrost soils revealed a diverse microbial population that are active at subzero temperatures although the activity is low (Gilichinsky et al, 2005;Gilichinsky & Rivkina, 2011;Rivkina et al, 2007). This microbial activity occurs primarily in the unfrozen water films/inclusions in the otherwise frozen soil, and this slow yet continuous long-term microbial metabolism could result in sustained winter time carbon flux (Fahnestock et al, 1999), spring thaw burst (Raz-Yaseef et al, 2017), and significantly change the soil biogeochemical characteristics.…”
Section: Permafrost Geochemistry and Biogeochemical Implicationsmentioning
confidence: 99%
“…There are a number of environments in the biosphere that could preserve viable microorganisms over geological time. Comparisons of the number of viable microorganisms preserved in galite and amber at temperatures above 0°С with those preserved in the cryosphere at temperatures below 0°С have shown that the cryosphere hosts a larger amount of extremely diverse viable microorganisms …”
Section: Cryospherementioning
confidence: 99%
“…Thus, the unfrozen water films are characterized as a major ecological niche for microorganisms . Because these water films are not thicker than several nanometers and are considerably smaller than the size of the microbial cells, cell growth, division (ie, reproduction) and movement within the films are unlikely . The amount of unfrozen water and the thickness of the water films are independent of ice content.…”
Section: Cryospherementioning
confidence: 99%
See 1 more Smart Citation